Barriers of Reporting Medication Errors at Arar Central Hospital, KSA - Alarfj, Abdulealah (Journal of medical and pharmaceutical sciences, 2020)
This study aimed to identify the barriers to reporting medication errors at Arar Central Hospital in Saudi Arabia. A descriptive cross-sectional survey of 241 health care providers was conducted at Arar Central Hospital (85 males and 156 females). The R-Studio assertion analysis program was used to identify factors considered as barriers to reporting medication errors. Confirmation factor analysis used to compare health care providers and factors influencing the reporting of medication errors. The results of the study showed that there were no differences between health care providers in the effect of the elements as they had the same measurements about the barriers to reporting medication errors. The results also indicated that fear factor is the most important obstacle behind the failure to report medication errors (32.37%), followed by the lack of information (15.7%) and that the lack of time is the least important obstacle Reporting medication errors (8.12%). In the light of the results, the study recommended that a non-punitive, protected, voluntary and simplified communication system should be implemented with an excellent response system if a root cause analysis error occurred, and health care providers should be encouraged to report medication errors. A future study is required to further investigate these and other factors and improve reporting rates.